A flutter-driven triboelectric nanogenerator for harvesting energy of gentle breezes with a rear-fixed fluttering film. (July 2022) - Tcho, Il-Woong; Kim, Weon-Guk; Kim, Jin-Ki; Kim, Do-Wan; Yun, Seong-Yun; Son, Joon-Ha; Choi, Yang-Kyu
Abstract: Wind energy is a promising renewable energy source in plentiful amounts. Mechanical energy harvesters can convert wind energy into electrical energy. Recently, the triboelectric nanogenerator (TENG) has been actively studied for harvesting mechanical energy. To harvest wind energy, various TENGs with a film fluttered by wind (flutter-driven wind-TENG, FW-TENG) have been proposed. The conventional FW-TENG has a front-fixed film, which faces a wind inlet and is fluttered solely by vortex shedding. In this work, a FW-TENG with a rear-fixed film (RFW-TENG) is demonstrated. A rear-fixed film is freestanding at the front that faces a wind inlet and fixed at the rear. Hence, the rear-fixed film in the RFW-TENG can be fluttered by a laminar flow as well as a vortex. The RFW-TENG can harvest the wind energy of gentle breezes, whereas some conventional FW-TENGs cannot. The RFW-TENG fabricated here with wedge-shaped protrusions and stoppers can harvest wind energy with a wide range of wind velocities from a gentle breeze to a windstorm. The RFW-TENG harnesses the wedge at both an upper and lower exoskeleton plate, which can cause the rear-fixed film to be easily separated from these plates, even under a gentle breeze. Moreover, a stopper installed in the RFW-TENG prevents the freestanding rear-fixed film from being curled inside the plates, and due to the nylon coating on the Al electrode of the fluttering film, the RFW-TENG can durably operate for a long time even at a high wind velocity. In a practical application, the RFW-TENG is shown to be able to supply electrical energy to commercial LEDs with natural wind outdoors. In addition, a self-powered dust-monitoring system linked to a smartphone is demonstrated with the RFW-TENG as an energy supplier. Graphical Abstract: ga1 Highlights: A flutter-driven TENG for harvesting wind energy with a rear-fixed film (RFW-TENG) is demonstrated. The RFW-TENG with wedge-shaped protrusions and stoppers can harvest wind energy with a wide range of wind velocities. Due to the nylon coating on the fluttering film, the RFW-TENG can operate for a long time even at a high wind velocity. A self-powered dust-monitoring system linked to a smartphone is demonstrated with the RFW-TENG as an energy supplier.